PV and Wind Energy Conversion Exploration based on Grid Integrated Hybrid Generation Using the Cuttlefish Algorithm - Nagaraja, Υ.; Devaraju, T.; Muni Sankar, A.; Narasimhulu, V. (Engineering, Technology & Applied Science Research, 2022)
This paper focuses on the exploration of grid-integrated hybrid generation comprising Photovoltaic (PV) and Wind Energy Conversion Systems (WECSs) using the Cuttlefish Algorithm (CFA). PV and wind energies are opposite because sunny days are normally calm, and strong winds frequently occur on cloudy days or at night. Hence, a hybrid PV and wind power system is more reliable than either individual source in terms of delivering uninterrupted power. The regulation of the DC voltage is the key issue in this configuration. The conventional PI controller is inaccurate in regulating the DC voltage. The PI controller gain tuning using optimization techniques provides good DC voltage regulation and less Total Harmonic Distortion (THD). Hence, CFA is proposed for the tuning of PI gains. The performance parameters such as DC voltage regulation and THD of CFA are analyzed.